2018
DOI: 10.4067/s0717-92002018000100151
|View full text |Cite
|
Sign up to set email alerts
|

Producción y composición de la hojarasca en un renoval pre andino de Nothofagus glauca de la región del Maule

Abstract: With the aim of advancing in the comprehension of Maulino forest functioning, the annual litter production and its specific composition in a young pre-Andean Maulino forest dominated by hualo (Nothofagus glauca) were estimated. For this, 30 litter traps of 0.25 m 2 were placed in three lines perpendicular to the slope on the floor of the forest. The litter was collected at variable intervals and separated into different components. During the three evaluated seasons, the annual mean production was 7.13 Mg ha-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Further analysis of this interval revealed that 75.1% of individuals were found on slopes between 20% and 40%, with 47.2% on slopes between 20% and 30%, and 30.5% between 25% and 30%. These results are consistent with other studies of Nothofagus species such as N. glauca, which also grows on steep slopes [36], and N. alpina, where slope conditions of around 43% have been identified [37].…”
Section: Discussionsupporting
confidence: 93%
“…Further analysis of this interval revealed that 75.1% of individuals were found on slopes between 20% and 40%, with 47.2% on slopes between 20% and 30%, and 30.5% between 25% and 30%. These results are consistent with other studies of Nothofagus species such as N. glauca, which also grows on steep slopes [36], and N. alpina, where slope conditions of around 43% have been identified [37].…”
Section: Discussionsupporting
confidence: 93%